The Mexican experience in monitoring and evaluation of public policies addressing social determinants of health - Adolfo Martinez Valle (Taylor & Francis Group, 2016)
Monitoring and evaluation (M&E) have gradually become important and regular components of the policy-making process in Mexico since, and even before, the World Health Organization (WHO) Commission on Social Determinants of Health (CSDH) called for interventions and policies aimed at tackling the social determinants of health (SDH). This paper presents two case studies to show how public policies addressing the SDH have been monitored and evaluated in Mexico using reliable, valid, and complete information, which is not regularly available. Prospera, for example, evaluated programs seeking to improve the living conditions of families in extreme poverty in terms of direct effects on health, nutrition, education and income. Monitoring of Prospera's implementation has also helped policy-makers identify windows of opportunity to improve the design and operation of the program. Seguro Popular has monitored the reduction of health inequalities and inequities evaluated the positive effects of providing financial protection to its target population. Useful and sound evidence of the impact of programs such as Progresa and Seguro Popular plus legal mandates, and a regulatory evaluation agency, the National Council for Social Development Policy Evaluation, have been fundamental to institutionalizing M&E in Mexico. The Mexican experience may provide useful lessons for other countries facing the challenge of institutionalizing the M&E of public policy processes to assess the effects of SDH as recommended by the WHO CSDH.